2024
DOI: 10.3390/w16020230
|View full text |Cite
|
Sign up to set email alerts
|

Responses of Soil and Ammonia Nitrogen Loss Rates to Hydraulic Parameters under Different Slope Gradients and Rainfall Intensities

Hao Yang,
Chenchen Wei,
Guanghui Sun
et al.

Abstract: Soil erosion and the consequent loss of nutrients have consistently been significant factors contributing to land degradation and nonpoint source pollution. While runoff serves as the primary carrier for nutrient loss, the hydraulic processes governing the mechanisms of nutrient loss remain not entirely clear. This paper aims to investigate the impacts of rainfall intensity and the slope gradient on hydraulic parameters, soil loss rates, and ammonia nitrogen loss rates, with the objective of determining the op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…The conclusion drawn was that both surface runoff and soil erosion on the slope increased with increasing rainfall intensity. However, the impact of the slope gradient was more complex, exhibiting different trends under varying rainfall intensities [28]. Wu Lei et al studied exposed loess under high rainfall intensity and found that, with an increase in rainfall duration, the sediment yield initially decreased rapidly before gradually stabilizing.…”
Section: Introductionmentioning
confidence: 99%
“…The conclusion drawn was that both surface runoff and soil erosion on the slope increased with increasing rainfall intensity. However, the impact of the slope gradient was more complex, exhibiting different trends under varying rainfall intensities [28]. Wu Lei et al studied exposed loess under high rainfall intensity and found that, with an increase in rainfall duration, the sediment yield initially decreased rapidly before gradually stabilizing.…”
Section: Introductionmentioning
confidence: 99%